Differences in baseline factors and survival between normocapnia, compensated respiratory acidosis and decompensated respiratory acidosis in COPD exacerbation: A pilot study. Issue 1 (8th October 2015) - Lun, Chung‐Tat; Tsui, Miranda S.N.; Cheng, Suet‐Lai; Chan, Veronica L.; Leung, Wah‐Shing; Cheung, Alice P.S.; Chu, Chung‐Ming
Abstract: Background and objective: Patients with chronic obstructive pulmonary disease (COPD) experiencing acute exacerbation (AE‐COPD) with decompensated respiratory acidosis are known to have poor outcomes in terms of recurrent respiratory failure and death. However, the outcomes of AE‐COPD patients with compensated respiratory acidosis are not known. Methods: We performed a 1‐year prospective, single‐centre, cohort study in patients surviving the index admission for AE‐COPD to compare baseline factors between groups with normocapnia, compensated respiratory acidosis and decompensated respiratory acidosis. Survival analysis was done to examine time to readmissions, life‐threatening events and death. Results: A total of 250 patients fulfilling the inclusion and exclusion criteria were recruited and 245 patients were analysed. Compared with normocapnia, both compensated and decompensated respiratory acidosis are associated with lower FEV1 % ( P  < 0.001), higher GOLD stage ( P  = 0.003, <0.001) and higher BODE index ( P  = 0.038, 0.001) and a shorter time to life‐threatening events ( P  < 0.001). Comparing compensated and decompensated respiratory acidosis, there was no difference in FEV1 (% predicted) ( P  = 0.15), GOLD stage ( P  = 0.091), BODE index ( P  = 0.158) or time to life‐threatening events ( P  = 0.301). High PaCO2 level ( P  = 0.002) and previous use of non‐invasive ventilation (NIV) in acute setting ( P  < 0.001) are predictive factors of future life‐threatening events by multivariate analysis. Conclusions: Compared with normocapnia, both compensated and decompensated respiratory acidosis are associated with poorer lung function and higher risk of future life‐threatening events. High PaCO2 level and past history of NIV use in acute settings were predictive factors for future life‐threatening events. Compensated respiratory acidosis warrants special attention and optimization of medical therapy as it poses risk of life‐threatening events. Abstract : In patients admitted with COPD exacerbation, compared with patients with normocapnia, both compensated and decompensated respiratory acidosis were associated with poorer lung function and higher risk of death/life‐threatening events. High PaCO2 level and history of NIV use in acute settings were predictive factors for life‐threatening events. Compensated respiratory acidosis warrants attention. Watch the video abstract